Evaluation of dietary supplement use for the improvement of the condition of skin and its appendages - Korzeniowska, Katarzyna; Cieślewicz, Artur; Pawlaczyk, Mariola; Pawlaczyk, Michał; Jabłecka, Anna (Journal of Medical Science, 2014)
Introduction. The condition of skin, nails and hair depends on a diet. Proper diet ought to include all components necessary to ensure a well-balanced intake of proteins, fats, carbohydrates, vitamins and elements. Dynamic development of the dietary supplement industry offers an expanding range of products aimed to improve the condition of skin, hair and nails. Aim. To study the issue of using dietary supplements aimed to improve skin and its appendages by men and women (in particular: studying the reason for such supplementation, determining the source of information about the supplements, evaluating the knowledge of the respondents and the effect of the supplements). Material and methods. The questionnaire-based study was conducted in 2013–2014, in a group of 115 people (65 women and 50 men), aged 16–60 years, who had been using dietary supplements designed to ensure proper appearance of the skin, hair or nails. Statistical analysis was carried out using StatSoft Statistica 10.0 software. Results. All participants had been using various dietary supplements for at least 4 months prior to the study commencement. 73% respondents declared that their main aim was to improve the condition of the skin, hair, and nails. The main reason for supplementation was the desire to improve the condition of the hair, reported by 48% of women and 64% of men. Both, women (59%) and men (48%) decided to supplement their diet mainly under the influence of the mass media. Considerable improvement in the condition of the skin and its appendages was observed by 79% of the respondents. Adverse effects were reported by 48% of the participants (with 72% concerning gastrointestinal tract). Conclusions. 1. Information provided by the mass media remains the main cause of purchase and consumption of dietary supplements. 2. Subjective efficiency of supplementation has been confirmed by the majority of the respondents. 3. Approximately half of the studied population reported adverse effects, especially on the gastrointestinal tract.